Self esteem sebagai moderator konformitas terhadap perilaku merokok elektrik (vape) - Merlyn Ika Rosyida Putri; Tulus Winarsunu; Djudiyah (Psychological Journal: Science and Practice, 2023)
A tobacco cigarette is an convensional cigarette. Beside a convensional cigarette there is an electric cigarette with liquid. So the smoker use it by sucking the liquid from the device of vape, then its produce much smoke. An elecric cigarette is more expensive than the convensional cigaratte and need special maintance. Vape is growing rapidly among the society moreever upper, midle, lower, teen and adult. The teenager tend to do conformity by following and copying adult to smoke E- cigarette or vape. Because they need to be recognized their existence in their circle. Therefore, we need self esteem to reduce or increase conformity behaviour. The aim of this study to examine the role of self esteem as a moderator of an effect the behaviour of teenager who use E-cigarette. There are 105 carats in this quantitative study. The writer took the sample directly by online and used purposive sampling technique through behaviour scale of smoking GNSBQ Glover-Nilson Smoking Behavioral Questionnaire, conformity scale and RSES Rosenberg self esteem scale. A modern analysis was conducted using Modeated Regression Analysis method (MRA) with 25 SPSS sofware. The result of this study shows that self esteem modern  has an effect to conformity of E-cigaratte bahaviour. The subject of self esteem can strengthen in increasing the effect of conformity effect to E- cigarette behaviour.